PENGARUH UKURAN PERUSAHAAN, AUDIT FEE, DAN KOMITE AUDIT TERHADAP TERJADINYA AUDITOR SWITCHING DENGAN DIMODERASI OLEH REPUTASI AUDITOR (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021) - Dhi'fan Hanif Arkaputra; Retnoningrum Hidayah (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
Auditor switching is a decision made by the company to change auditors and Public Accounting Firms (KAP). One of the objectives is to improve audit independence and quality. Auditor Switching carried out by a company can be divided into two reasons, the first is due to regulations issued by the government that must be implemented (mandatory) and the second is based on the wishes of the company itself which is voluntary. In this study, a moderating variable of auditor reputation was also added. The purpose of this study was to analyze firm size, audit fees, and audit committee on auditor switching with auditor reputation as a moderating variable. This study uses secondary data with a population of all banking sector companies listed on the IDX in 2017-2021. Sampling of 25 companies. The analysis used in this study is logistic regression analysis. The analytical tool used is WarpPLS version 7.0. The results of this study indicate that firm size has an effect on auditor switching. Meanwhile, the audit fee and the audit committee have no effect on auditor switching. Audit reputation cannot moderate firm size, but audit reputation can moderate the effect of audit fees and audit committees. Future research is also expected to use other broader company sectors with the latest and longer terms. In addition, auditor switching can also be seen from the same grade, downgrade, or upgrade KAP category.